Safety and efficacy of intravenous thrombolysis for acute ischemic stroke secondary to intracranial vertebrobasilar artery dissection - Wang, Nuo; Liu, Wei; Lin, Huangbin; Deng, Benqiang; Zhao, Kaijun; Wu, Tao (Frontiers in Neurology, 2025)
ObjectiveThe safety and effectiveness of thrombolysis in patients with intracranial artery dissection (IAD) are still controversial. This study aims to assess the safety and efficacy of intravenous thrombolysis (IVT) in patients with intracranial vertebrobasilar artery dissection (i-VBAD) related acute ischemic stroke (AIS).MethodsA retrospective review of 32 patients admitted to our Neurovascular Center between January 2016 and June 2021 with AIS due to i-VBAD was conducted. Patients were identified and divided into IVT group (n = 8) and non-IVT group (n = 24) receiving standard antithrombotic therapy.ResultsThe mean age of the 32 patients was 49.28 ± 15.6 years, with a male predominance (87.5%). All patients presented with clinical manifestations consistent with posterior circulation infarct. Patients in the IVT group were significantly older than those in non-IVT group (58.88 vs. 46.08 years, p = 0.043) and had a higher prevalence of diabetes mellitus (50.0% vs. 8.3%, p = 0.023). No intracranial hemorrhage was observed in of the eight patients in IVT group. An excellent functional outcome, defined as an modified Rankin Scale score of 0–1, was achieved in all eight patients in the IVT group (100%) compared to 15 of the 24 patients in the non-IVT group (62.5%, p = 0.070). Although the difference did not reach statistical significance, the trend suggested a potential benefit of IVT in this patient population.ConclusionIVT appears safe with no hemorrhagic complications in i-VBAD patients. It may offer better functional outcomes compared to standard therapy. Larger, prospective, multicenter studies are needed for definitive validation.